A Universal DNA Aptamer that Recognizes Spike Proteins of Diverse SARS‐CoV‐2 Variants of Concern. Issue 15 (18th February 2022) - Zhang, Zijie; Li, Jiuxing; Gu, Jimmy; Amini, Ryan; Stacey, Hannah D.; Ang, Jann C.; White, Dawn; Filipe, Carlos D. M.; Mossman, Karen; Miller, Matthew S.; Salena, Bruno J.; Yamamura, Deborah; et al.
Abstract: We report on a unique DNA aptamer, denoted MSA52, that displays universally high affinity for the spike proteins of wildtype SARS‐CoV‐2 as well as the Alpha, Beta, Gamma, Epsilon, Kappa, Delta and Omicron variants. Using an aptamer pool produced from round 13 of selection against the S1 domain of the wildtype spike protein, we carried out one‐round SELEX experiments using five different trimeric spike proteins from variants, followed by high‐throughput sequencing and sequence alignment analysis of aptamers that formed complexes with all proteins. A previously unidentified aptamer, MSA52, showed K d values ranging from 2 to 10 nM for all variant spike proteins, and also bound similarly to variants not present in the reselection experiments. This aptamer also recognized pseudotyped lentiviruses (PL) expressing eight different spike proteins of SARS‐CoV‐2 with K d values between 20 and 50 pM, and was integrated into a simple colorimetric assay for detection of multiple PL variants. This discovery provides evidence that aptamers can be generated with high affinity to multiple variants of a single protein, including emerging variants, making it well‐suited for molecular recognition of rapidly evolving targets such as those found in SARS‐CoV‐2. Abstract : This is a unique one : A unique DNA aptamer has been discovered that has the ability to recognize the spike proteins of the wildtype SARS‐CoV‐2 and its seven current variants of concern (VoCs), including B.1.1.7, B.1.351, P.1, B.1.429, B.1.617.1 B.1.617.2 and B.1.1.529 and is predicted to recognize the spike proteins of future VoCs.